The contribution of high-quality food production to endogenous rural development in Umbria, Central-Italy - van der Meulen H.; Ventura F. (Strengthening endogenous development patterns in European agriculture, 1993)
With a wide range of local examples on high-quality food production, this paper is in first place a theoretical contribution to the debate on the concept of endogenous rural development. On the other hand it offers a practical contribution to the question of how endogenous rural development can be propelled by specific research and intervention in the field of high-quality food production.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)